A New Pilgrimage in Portugal: Following the Steps of Saint Nuno - Braga, Carla; Brito, Miguel; Soares, Margarida (Dublin Institute of Technology, Leeds Metropolitan University, 2013)
Tourism is an ever-changing reality. Pilgrimages need different stimuli to attract new followers. In this context we propose to create an itinerary following the steps of Saint Nuno of Santa Maria, canonized in 2009. Nuno Álvares Pereira was the real name of Saint Nuno, who was granted the title Constable of Portugal, and became a historic legend in the independence wars of Portugal during the political crisis of 1383-1385. After fighting against the power of Castile(Spain) he decided to devote his life to religion as a Carmelite Friar. He represents the perfect hero of the Middle Ages - associating military prowess with a religious character. Our proposal is to create a religious itinerary based on facts of Saint Nuno’s life, so that any visitor may easily discover the country following the steps of this saint who was deeply devoted to the Virgin - in fact, all temples he founded and restored were dedicated to Our Lady. One of his most famous foundations is the Carmelite Convent in Lisbon, which long after his death was an outstanding popular pilgrimage place, and today is still a strong visitor attraction. This exploratory study is based on literature review and text analyses about religious tourism, itinerary design and the life of the saint. The fieldwork includes acknowledging the different sites related to the saint. We believe that it is possible to create an original religious itinerary in Portugal, which will attract not only foreigners but also domestic visitors, increasing the ‘Production and Consumption of the Pilgrimage Tourism Experience’.
Keywords: Saint Nuno; Pilgrimage; Itineraries; Portugal; São Nuno; Peregrinação; Itinerários